(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is devoted to the study of the changes being implemented in the education system in Uzbekistan in terms of modernization and introduction of new innovative pedagogical technologies. In particular, the article discusses the cooperative learning model in teaching English. This model is aimed at developing mutual learning and social skills of students through joint work. Detailed information is provided on the main principles of cooperative learning, including intergroup interdependence, individual responsibility, mutual assistance and support, and the development of social skills. The article also analyzes the contribution of cooperative learning to academic achievement, acceptance of social diversity, and the development of critical thinking.